Perceptions of Culinary MSMEs toward the Implementation of MPOS and TMD in Encouraging Voluntary Tax Compliance in North Toraja - Wilma Dian Ardiyanti; Srisetyawanie Bandaso; Isar Tandi Allo; Krismayanti Pare Sulo (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to describe the perceptions of culinary MSME actors toward the implementation of MPOS and TMD, to explore the experiences of culinary MSME actors in using MPOS and TMD, and to understand how the implementation of MPOS and TMD influences the voluntary tax compliance of culinary MSME actors in North Toraja. This research used a descriptive qualitative approach; data were collected through in-depth interviews with MSME actors who had used MPOS and TMD. The results of the study show that MSME actors have positive perceptions of MPOS and TMD because they are considered to assist transaction recording, enhance transparency, and simplify tax calculation. However, this system still faces various technical constraints, including network disruptions, power outages, system errors, paper shortages for receipts, and resistance from some customers to paying taxes. MSME actors also offered several suggestions, including the need for Bapenda's assistance and routine monitoring, improvements to the application, and more intensive socialization. This study concludes that MPOS and TMD have the potential to enhance voluntary tax compliance; however, their effectiveness largely depends on infrastructure readiness and local government support.